Back to the Future. The Future in the Past. Conference Proceedings Book - Oriol Moret (ed.) (Col·lecció Singularitats, 2018)
ICDHS is the acronym of the International Committee of Design History and Design Studies, an organisation that brings together scholars from Spain, Cuba, Turkey, Mexico, Finland, Japan, Belgium, the Netherlands, Brazil, Portugal, the US, Taiwan, Canada and the UK. Since 1999, when the Design and Art History departments of the University of Barcelona organised the first edition of the ICDHS, a conference has been held every two years at a different venue around the world. These conferences have had two distinct aims: first, to present original research in the fields of Design History and Design Studies and, second, to include contributions in these fields from non-hegemonic countries, offering a speaking platform to many scientific communities that are already active or are forming and developing. For that reason, the structure of the conferences combines many parallel strands, including poster presentations and keynote speakers who lecture on the conferences' main themes. The 2018 event is rather special. The Taipei 2016 conference was the 10th edition and a commemoration of the ten celebrations to date. Returning to Barcelona in 2018 marks the end of one stage and the beginning of a new one for the Committee. The numbering chosen-"10+1"-also means that Barcelona 2018 is both an end and a beginning in the ICDHS's own history. The book brings together 137 papers delivered at the ICDHS 10th+1 Conference held in Barcelona on 29-31 October 2018. The papers are preceded by texts of the four keynote lectures and a written tribute from the ICDHS Board to its founder and figurehead, Anna Calvera (1954-2018). The Conference, and the book, are dedicated to her memory.